POLA KOMUNIKASI PENYULUH PERTANIAN LAPANGAN (PPL) DI KECAMATAN WUA-WUA KOTA KENDARI - Antika, Windi; Rela, Iskandar Zainudin; Wunawarsih, Ima Astuty (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The development of hydroponic agriculture as a solution to land limitations in urban areas in Kendari City requires effective agricultural extension support, particularly through participatory, dialogic, and adaptive PPL communication patterns in order to increase farmers' capacity to adopt hydroponic technology. The objective of this study is to analyze the communication patterns exhibited by agricultural extension workers when interacting with hydroponic farmers in Wua-Wua District, Kendari City. The research population comprised all hydroponic farmers in Wua-Wua District, Kendari City. The research sample was obtained through the census method, yielding a total of 30 individuals. The data were collected through surveys, questionnaires, documentation, and literature studies. The research variable was defined as the communication patterns exhibited by agricultural extension workers. The analysis was performed using descriptive analysis. The findings indicated that the communication patterns exhibited by field agricultural extension workers (PPL) in Wua-Wua District, Kendari City, demonstrated that unidirectional communication predominantly fell within the adequate range, with limited potential for enhancement, particularly in enhancing the comprehension of hydroponic farmers. This is attributable to constrained interaction and feedback. Conversely, bidirectional and multidirectional communication exhibited a predominance of the good category, exhibiting efficacy in fostering active participation, dialogue, and contextual learning among farmers. Two-way communication patterns facilitate the exchange of information that is responsive to technical problems in the field, while multi-way communication patterns enhance social learning through collaboration between farmers and related parties, thereby supporting the improvement of understanding and the sustainable application of hydroponic technology. The efficacy of agricultural extension in urban areas is predominantly contingent upon the capacity of extension workers to employ participatory and dialogical communication methodologies.